Multi-task learning for simultaneous script identification and keyword spotting in document images. (May 2021) - Cheikhrouhou, Ahmed; Kessentini, Yousri; Kanoun, Slim
Abstract: In this paper, an end-to-end multi-task deep neural network was proposed for simultaneous script identification and Keyword Spotting (KWS) in multi-lingual hand-written and printed document images. We introduced a unified approach which addresses both challenges cohesively, by designing a novel CNN-BLSTM architecture. The script identification stage involves local and global features extraction to allow the network to cover more relevant information. Contrarily to the traditional feature fusion approaches which build a linear feature concatenation, we employed a compact bi-linear pooling to capture pairwise correlations between these features. The script identification result is, then, injected in the KWS module to eliminate characters of irrelevant scripts and perform the decoding stage using a single-script mode. All the network parameters were trained in an end-to-end fashion using a multi-task learning that jointly minimizes the NLL loss for the script identification and the CTC loss for the KWS. Our approach was evaluated on a variety of public datasets of different languages and writing types.. Experiments proved the efficacy of our deep multi-task representation learning compared to the state-of-the-art systems for both of keyword spotting and script identification tasks.